The Role Of Lontar Digitalization For Hinduism Informal Education In Preserving Cultural And Hinduism At The Puri Gede Kerambitan Tabanan - I Putu Putra Yasa; I Nengah Duija; I Wayan Wastawa (Institut Hindu Dharma Negeri Denpasar, 2018)
Bali having many literary work in form of lontar which is stored in a library or collection of personal. Overall, it cannot be known for certain but mostly to lack of care. The lontar contain to the transcendent value the teachings of Hinduism that can be implemented in life. This research revealed about the preservation of cultural and Hinduism through the efforts of lontar digitalization which is then associated with the role of Hinduism informal education especially at Puri Gede Kerambitan. The focus of research are: lontar digitalization process, the role of the lontar digitalization to Hinduism informal education, and the efforts that supports lontar digitalization. The purpose of this research are: provides a description of lontar digitalization at Puri Gede Kerambitan, explaining the role of the process of lontar digitalization to Hinduism informal education and provides a description of supporting efforts lontar digitalization. Disclosure of research results was done through qualitative arguments. The results of this study indicate that are (1) Lontar is cultural documentation of the past that is highly valued. The preservation of lontar by doing lontar digitalization can provides a description about the conversion of the lontar into the form of digital image by using digital equipments. Lontar digitalization as a positive step to save the literature about culture and Hinduism that is highly valued; (2) Lontar digitalization has a positive for the process of Hinduism informal education by applying values of Hinduism directly during the performance of lontar digitalization; (3) Puri Gede Kerambitan gives full support to the lontar digitalization process that has been conducted by outsiders. But the Government support is still not maximum yet to the preservation of culture and Hinduism. The efforts made by various parties were the overview of insights and viewpoints that support the preservation of lontar through lontar digitalization.